1994
DOI: 10.1590/s0103-90161994000200015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and nitrogen levels on qualitative and nutritional aspects of fig-trees (Ficus carica L.)

Abstract: In order to evaluate qualitative and nutritional aspects of fig-trees with respect to six irrigation and six nitrogen levels, at Ilha Solteira, SP, Brazil, an experiment was carried out in randomized blocks, with subdivided plots, and four replications. Results showed that in four dates during harvest, only the first analysis (January 2, 1991) showed influence of nitrogen fertilization on fruit soluble solids (brix). There was no significant effect of treatments on pulp/peel relation for the four harvestings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The average crop yields were (7 517 and 6 597) kg·ha -1 , respectively, with and without cattle manure addition (table IV). Hernandez et al [20] reported that, for a fruit yield of 10 t·ha -1 of ripe figs and (table VII). Proebsting and Warner [22], studying Adriatic and Calimyrna fig varieties, evaluated the N, P, K, Ca and Mg leaf contents between April and September; they observed that the N and P contents decreased with plant development; the K contents showed an unusual tendency, that is, there was a great increase in leaf content between April and June, decreasing thereafter until September; the Ca and Mg contents increased during the period April to September.…”
Section: Amounts Of Nutrients Extracted Per Hectare Per Crop Yieldmentioning
confidence: 94%
“…The average crop yields were (7 517 and 6 597) kg·ha -1 , respectively, with and without cattle manure addition (table IV). Hernandez et al [20] reported that, for a fruit yield of 10 t·ha -1 of ripe figs and (table VII). Proebsting and Warner [22], studying Adriatic and Calimyrna fig varieties, evaluated the N, P, K, Ca and Mg leaf contents between April and September; they observed that the N and P contents decreased with plant development; the K contents showed an unusual tendency, that is, there was a great increase in leaf content between April and June, decreasing thereafter until September; the Ca and Mg contents increased during the period April to September.…”
Section: Amounts Of Nutrients Extracted Per Hectare Per Crop Yieldmentioning
confidence: 94%
“…[20], avaliando plantas com 12 ramos, na terceira colheita de frutos maduros, observaram médias de comprimento de frutos variando de 42,9 a 52,9 mm e diâmetro de 39,8 a 47 mm, valores bem inferiores ao presente trabalho e aos relatados por PEREIRA [35], que descreveu frutos com comprimento de 75 mm. Isto se deve ao fato de os estudos terem sido realizados em condições edafoclimáticas diferentes, tendo a planta um comportamento característico para cada região.…”
Section: -Atributos Físicosunclassified